How Great Generals Win - Alexander, Bevin (Lahore Army Education Press, 1993)
Alexander analyzes the mindset that distinguishes a truly great commander from a merely good one. Includes Hannibal, Genghis Khan, Napoleon, Stonewall Jackson, Sherman, Rommel, Mao Zedong, and many others.
Includes Illustration, Bibliography and Index
Keywords: Military Art and Science -- Generals -- Battles